Training in a virtual environment for high risk work at heights. (14th December 2021) - Scott, Sandra; Tichon, Jennifer; Hine, Trevor J.
Falls from a height are a common reason for workplace fatalities in the construction industry. Such high-risk work is likely to remain inherent in construction tasks requiring further efforts to reduce the risk of falling. As an underlying instability in balance may promote the development of height phobia, the current study investigated the role of fear of heights, and individual's postural response (PR) to the perturbation of an elevated work platform while exposed to simulated heights scenarios in virtual reality (VR). Postural responses were measured during the VR training experiment and the Acrophobia questionnaire and motion sickness susceptibility questionnaire were administered. Results indicated that the height anxiety (a sub-scale of the acrophobia questionnaire) was reduced after the 50-minute VR session comprising five trials. Postural response improvement also correlated with decreases in fear of heights. Findings indicate that construction workers may benefit from inclusion of VR exposure to heights as part of preparation to work at heights.